Aggravating and Relieving Factors of Migraine and Tension Type Headache in the adult general population of Karachi, Pakistan - Ahmed khan, Ubaid; Sarwat, Surriyya; Amin, Mawara; Hamid, Sadaf; Hussain, Muhammad Ammad (Journal of Liaquat University of Medical & Health Sciences, 2025)
Objective: To determine the common aggravating and relieving factors among tension-type headache patients. METHODOLOGY: This study employed a cross-sectional design, with data collected from patients who frequently visited the outpatient neurology clinic at M. Rab Medical Centre and the neurology clinic. The study duration was one year, and the sample size was calculated using the online software Open Epi. At a 95% confidence level, the resulting sample size consisted of 500 participants from both sexes and the data collection instrument was a structured questionnaire. RESULTS: All study responses included both males (30.6%) and females (69.4%). It revealed that the most common aggravating factors increasing the intensity of headaches were Stress and anxiety (64%) along with sleep deprivation (61.4%) as well as exposure to loud noise. Regarding the reliving factors, it was revealed that 71.2% of individuals showed a significant reduction in headache intensity with Sleep, while Tea was identified as a relieving factor among 258 individuals (51.6%). Other interesting factors were also identified, including Ablution and recitation of the Holy Quran. CONCLUSION: The study revealed that migraine and tension-type headaches in Karachi’s adult population are exacerbated by factors such as anxiety, bright lights, hunger, loud noises, family problems, and insufficient Sleep. These causes differ among genders, age groups, and individuals. Women are more sensitive to anxiety, loud noises, and family problems, while younger individuals are more affected by bright lights and excessive Sleep.